APPLICATION OF INDIGENOUS HERBAL EXTRACTS TO CONTROL ASPERGILLUS FLAVUS THE AFLATOXIN-PRODUCING FUNGUS IN PEANUTS - Sehawong, Wimonsiri; Aroonluk, Suvichark; Subepang, Sayan (Life Sciences and Environment Journal, 2025)
This study focuses on the use of indigenous herbs from Sisaket province, namely garlic (Allium sativum) and shallot (Allium ascalonicum), to evaluate their efficacy in inhibiting the growth of Aspergillus flavus, a fungal species responsible for aflatoxin contamination in peanuts. Herbal extracts were prepared at concentrations of 5% and 10% and incorporated into PDA culture medium. The experimental design followed a completely randomized design (CRD) with three replications per treatment. Fungal colony diameters were measured on days 3, 5, and 7 after-inoculation, and the inhibition percentages were calculated accordingly. The results demonstrated that the 10% garlic extract exhibited the highest antifungal activity, reducing the average colony diameter to 1.75 ± 0.71 cm with an inhibition rate of 52.55%. This was followed by shallot 10%, garlic 5%, and shallot 5% treatments, respectively. Statistical analysis confirmed significant differences among treatments (p ≤ 0.05), indicating a concentration-dependent antifungal effect. The biological activity of the herbal extracts is likely attributed to their organosulfur compounds and volatile oils naturally found in garlic and shallots. These findings suggest that local herbal extracts, particularly 10% garlic extract, offer a promising and eco-friendly alternative for mitigating aflatoxin contamination in peanuts. This approach supports sustainable agriculture, reduces dependency on synthetic fungicides, and aligns with food safety and public health standards.